Atomic Dispersed Hetero-Pairs for Enhanced Electrocatalytic CO2 Reduction - Jin, Zhaoyong; Yang, Meiqi; Dong, Yilong; Ma, Xingcheng; Wang, Ying; Wu, Jiandong; Fan, Jinchang; Wang, Dewen; Xi, Rongshen; Zhao, Xiao; Xu, Tianyi; Zhao, Jingxiang; et al. (Nano-Micro Letters, 2023)
Electrochemical carbon dioxide reduction reaction (CO2RR) involves a variety of intermediates with highly correlated reaction and ad-desorption energies, hindering optimization of the catalytic activity. For example, increasing the binding of the *COOH to the active site will generally increase the *CO desorption energy. Breaking this relationship may be expected to dramatically improve the intrinsic activity of CO2RR, but remains an unsolved challenge. Herein, we addressed this conundrum by constructing a unique atomic dispersed hetero-pair consisting of Mo-Fe di-atoms anchored on N-doped carbon carrier. This system shows an unprecedented CO2RR intrinsic activity with TOF of 3336 h−1, high selectivity toward CO production, Faradaic efficiency of 95.96% at − 0.60 V and excellent stability. Theoretical calculations show that the Mo-Fe diatomic sites increased the *COOH intermediate adsorption energy by bridging adsorption of *COOH intermediates. At the same time, d-d orbital coupling in the Mo-Fe di-atom results in electron delocalization and facilitates desorption of *CO intermediates. Thus, the undesirable correlation between these steps is broken. This work provides a promising approach, specifically the use of di-atoms, for breaking unfavorable relationships based on understanding of the catalytic mechanisms at the atomic scale. Highlights: 1 A unique atomic dispersed hetero-pair was successfully synthesized, consisting of Mo-Fe di-atoms anchored on N-doped carbon carrier. 2 This strategy breaks the linear scaling relationships of electrocatalytic CO2 reduction by simultaneously regulating the *COOH adsorption energy and *CO desorption energy. 3 The as-prepared MoFe–N–C exhibits excellent performance for CO2RR to CO with a high turnover frequency (TOF) of 3336.21 h−1, CO Faradaic efficiency (FECO) of 95.96% at − 0.60 V (versus RHE) and outstanding stability.